1991
DOI: 10.1002/1097-0142(19910501)67:9<2327::aid-cncr2820670919>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a new cell line TC-YIK originating from argyrophil small cell carcinoma of the uterine cervix integrating HPV16 DNA

Abstract: A new cell line, designated TC-YIK, was established from YIK-1 tumor cells, derived from argyrophil small cell carcinoma (ASCC) of the uterine cervix, and serially heterotransplanted into nude mice, integrating human papillomavirus type 16 (HPV16) DNA. The population doubling time of TC-YIK was approximately 21.6 hours at the 119th subculture. Subcutaneous injection of 1 x 10(8) TC-YIK cells into nude mice yielded a solid tumor. The cytologic appearance of TC-YIK was similar to that of YIK-1. The TC-YIK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…SCCC is a rare cancer with a poor prognosis and biological features that are not well elucidated. As a research platform, even conventional cell lines are quite rare . We demonstrated here that CTOS lines of SCCC were easily and efficiently established from surgical samples and used them as an example, applying radiation therapy technology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…SCCC is a rare cancer with a poor prognosis and biological features that are not well elucidated. As a research platform, even conventional cell lines are quite rare . We demonstrated here that CTOS lines of SCCC were easily and efficiently established from surgical samples and used them as an example, applying radiation therapy technology.…”
Section: Discussionmentioning
confidence: 97%
“…As a research platform, even conventional cell lines are quite rare. 28,29 We demonstrated here that CTOS lines of SCCC were easily and efficiently established from surgical samples and used them as an example, applying radiation therapy technology. The success rates of CTOS preparation and culture are 98.7% in colorectal cancer, 16 80.0% in lung cancer 18 and 84.2% in bladder cancer.…”
Section: Discussionmentioning
confidence: 97%
“…[8][9][10] In our previous studies, we found that TC-YIK cells retained the histochemical characteristics of ASCC cells and could be used as an in vitro experimental model of ASCC, and that the TC-YIK cells were possibly of neuroendocrine origin, based on electron microscopic evidence of small, electron-dense, membrane-bound neurosecretory-type granules and immunohistochemical evidence of neuron-specific enolase, chromogranin, serotonin and gastrin. 8,9,11) In terms of the origin of ASCC, however, there have been three theories: ASCC originates from (i) amine precursor uptake and decarboxylation (APUD) cells, 2,3,12) (ii) undifferentiated epithelial cells with multi-differentiation ability, 13) or (iii) stem cells. …”
mentioning
confidence: 58%
“…Isolation and characterization of TC-YIK cells are described elsewhere. 9,10) TC-YIK cells were cloned twice after 60 cell generations from the start of culture using the limiting dilution method. The clone that showed the most stable growth was used for the current study.…”
Section: Methodsmentioning
confidence: 93%
“…Therefore, development of in vivo and in vitro experimental systems is desirable not only for examining the biologic behavior of ASCC, but also for establishing an effective clinical treatment for the tumor. We reported previously the establishment and Characterization of an ASCC tumor line in nude mice and also a cell line from the tumor, designated TC-YIK (Ichimura et al, 1988(Ichimura et al, , 1991. In our previous study, we briefly rcportcd TC-YIK cells to be possibly of neuroendocrine origin based on the demonstration of small, electron-dense, membrane-bound neurosecretory-type granules by an electron microscopic study and positive staining for neuron-specific enolase, chromogranin, serotonin and gastrin by an immunohistochemical study (Ichimura ef a/., 1991).…”
mentioning
confidence: 99%